Cost, Quality, and Accessibility: A Comparative Analysis of Business Profiles in Public and Private Healthcare Institutions - А Literature Review - Abashidze, Salome; Taktakishvili, Tengiz; Abashidze Gabaidze, Gulnara (European Scientific Journal, ESJ, 2026)
Aims and Objectives: The main objective of the research is to study the differences between public and private healthcare institutions in terms of cost, service quality, and accessibility. Methods: The paper is a systematic literature review based on the PRISMA guidelines. The materials were searched in international scientific databases: PubMed, Elsevier, Scopus, and Google Scholar. The study includes an analysis of peer-reviewed international articles published in the last 10 years. Of the 182 records initially identified, 98 remained after removing duplicates and ineligible records. After screening titles and abstracts, 33 articles met the inclusion criteria and were used for the final synthesis. Results: The evidence synthesis showed that systems with strong public funding are more effective in reducing patients’ out-of-pocket costs and ensuring financial protection. The private sector is distinguished by its promptness of service, reduced waiting times, and a patient-centered approach, although this is often associated with high costs and does not always translate into improved clinical outcomes. It was revealed that the creation of a unified e-health network significantly improves cost-effectiveness and collaboration between sectors. Findings and Conclusion: The study concludes that neither the public nor the private sector can achieve full efficiency and equity independently. A balanced hybrid approach is considered the optimal model for progress towards universal health coverage (UHC). It is recommended that public policymakers increase public funding, strengthen public-private partnerships (PPPs), and scale up electronic systems, ensuring equitable access to quality healthcare services and system sustainability.